2007
DOI: 10.1166/jnn.2007.723
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Spectroscopy of Multiwalled Carbon Nanotubes: A Simple Approachto Study the Nitrogen Doping

Abstract: The nitrogen doped multiwalled carbon nanotubes (MWNTs) were synthesized by microwave plasma chemical vapor deposition (MPCVD) technique. In this paper, we report the results of FTIR, Raman, and TGA studies to confirm the presence of N-doping inside carbon nanotubes. Fourier transform infrared (FTIR) studies were carried out in the range 400-4000 cm(-1) to study the attachment of nitrogen impurities on carbon nanotubes. FTIR spectra of the virgin sample of MWNTs show dominant peaks which are corresponding to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(45 citation statements)
references
References 0 publications
2
42
0
1
Order By: Relevance
“…The IR spectrum of CNT shows absorption band at 2920 cm −1 which is attributed to asymmetric and symmetric CH 2 stretching, 1698 cm −1 assigned to carboxylic CïŁŸO stretching and 1097 cm −1 corresponding to CïŁżO stretching in alcohols. The presence of these functional groups on the surface of CNT indicates their introduction during removal of metal catalysts in the purification processes of CNT 22, 23. Carboxylic CïŁŸO stretching peak observed at 1693 cm −1 can be attributed to acid treatment of CNT.…”
Section: Resultsmentioning
confidence: 97%
“…The IR spectrum of CNT shows absorption band at 2920 cm −1 which is attributed to asymmetric and symmetric CH 2 stretching, 1698 cm −1 assigned to carboxylic CïŁŸO stretching and 1097 cm −1 corresponding to CïŁżO stretching in alcohols. The presence of these functional groups on the surface of CNT indicates their introduction during removal of metal catalysts in the purification processes of CNT 22, 23. Carboxylic CïŁŸO stretching peak observed at 1693 cm −1 can be attributed to acid treatment of CNT.…”
Section: Resultsmentioning
confidence: 97%
“…Comparison between spectra of pristine nanotubes and oxidized N-MWCNTs showed that the bands at 1444 cm -1 , 1373 cm -1 and 1251 cm -1 , attributed to vibration of MWCNTs and C-N bonding in N-MWCNTs, were overcome by several vibrations in carbonyl and carboxylic functionalities in the range of 1720 to 1250 cm -1 (Choi et al, 2004;Misra et al, 2007). A strong band appeared from 3600 cm -1 to 3300 cm -1 by the stretching of the bonding -OH of carboxylic group in oxidized nanotubes (Zawadski, 1980;Chen and Wu, 2004).…”
Section: Ftir Characterization Of Oxidized Carbon Nanotubesmentioning
confidence: 99%
“…This can be ascribed to the hydrophobic adsorbed DMF on the CNTs surface or by -interaction as well as the Columbic or hydrophilic interaction minimization after DMF sonication which de-bundled the CNTs [10]. [11][12][13]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Peaks at 1093 and 1388 cm −1 represent C H symmetrical mode [6,11]. Misra et al identified this peak at 1440 cm −1 as unique to MWCNTs [12]. The band around 1582 cm −1 can be attributed to graphite structure in MWNTs [11] while C C stretching vibration bond appears at ∌1668.43 cm −1 , suggests the formation of carbon nanoparticles [13].…”
Section: Resultsmentioning
confidence: 99%